Menstrual-cycle characteristics and work conditions of workers in poultry slaughterhouses and canneries. - Messing, Karen; Saurel-Cubizolles, M. J.; Bourgine, M.; Kaminski, M. (Scandinavian Journal of Work, Environment & Health, 1992)
The food and agriculture industry employs 14.6% of the female industrial work force in France. Workers are exposed to a variety of environmental and organizational constraints (eg, irregular schedules, cold, uncomfortable postures, repetitive movements). In 1987-1988 a medical examination and questionnaire were administered to 726 workers with menstrual periods in 17 poultry slaughterhouses and six canning factories. Anomalies (irregular cycles, amenorrhea, long cycles) during the previous year were associated with work conditions. After adjustment for relevant nonoccupational variables, irregular cycles were significantly related to schedule variability and cold exposure, amenorrhea was associated with cold exposure, and long cycles with schedule variability. Other parameters such as repetitive work, standing posture, lifting weights, job satisfaction, and hours of domestic work were not associated with cycle anomalies. Cycle anomalies may be a useful indicator of occupational effects on female reproduction, analogous to the use of sperm parameters to warn of effects on male workers.